Revolution and Economic Growth: Evidence from the Sandinista Revolution - Filippo Silano (University of Hamburg, Institute of Law and Economics (ILE), 2023)
This study examines the repercussions of the 1979 Sandinista revolution on Nicaragua's economic growth trajectory. Drawing on the synthetic control method, it constructs an artificial counterpart to Nicaragua with the primary objective of estimating the counterfactual gross domestic product (GDP) per capita growth rate, assuming that the revolution did not take place. By doing so, the study quantifies the extent to which the Sandinista revolution influenced the country's economic development. The results show that the Somoza removal and the immediate implementation of the Sandinistas policies led to a slight improvement of GDP per capita's growth rate (+2%). On the other hand, the civil war's intensification that ensued (1984-87) negatively affected the initial positive effect of the revolutionary government policy making. This study contributes to a better understanding of the economic dynamics associated with revolutions and civil wars. The findings underscore the significance of considering the broader context in assessing historical events' economic implications and call for further research into the long-term effects of such institutional and political transformations.
Keywords: O54; N46; P16; P26; C21; H56; 330; Sandinista; Nicaragua; Revolution; Civil war; Synthetic control method; Economic growth; Economic development; Political economy